2017
DOI: 10.2139/ssrn.3035335
|View full text |Cite
|
Sign up to set email alerts
|

Trading Offshore: Evidence on Banks' Tax Avoidance

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…Their key findings are that banks' response to taxation is stronger compared to a consensus estimate of studies analyzing non-banks' profit shifting and that trading gains are highly responsive. This finding is corrobated by Langenmayr and Reiter (2017) who show that German banks relocate their trading gains to low-tax countries to benefit from the low tax rate while the employees conducting the trade remain in the headquarter, i.e. the high-tax country.…”
Section: Hypothesis Development and Related Literaturementioning
confidence: 94%
See 3 more Smart Citations
“…Their key findings are that banks' response to taxation is stronger compared to a consensus estimate of studies analyzing non-banks' profit shifting and that trading gains are highly responsive. This finding is corrobated by Langenmayr and Reiter (2017) who show that German banks relocate their trading gains to low-tax countries to benefit from the low tax rate while the employees conducting the trade remain in the headquarter, i.e. the high-tax country.…”
Section: Hypothesis Development and Related Literaturementioning
confidence: 94%
“…One the one hand, several studies (e.g. Demirgüç-Kunt andHuizinga (2001), Merz andOveresch (2016), Langenmayr and Reiter (2017), Shaxson (2018)) and governmental reports (e.g. OECD (2009), OECD (2010), and OECD (2011)) emphasize that banks have either more or other 9 As far as we know there is no study that explicitly looks at the level of tax avoidance and tax avoidance determinants for banks and compares the outcomes to non-banks.…”
Section: Hypothesis Development and Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The underlying reason is that a purely domestic group has no possibility and incentive to shift profits cross-border, and therefore the CbCR does not provide any incremental information on 7 These studies document a tax semi-elasticity of banks' overall reported profits of about 2.4 (Merz & Overesch, 2016) and of certain trading gains of about 3.4 to 4.0 (Merz & Overesch, 2016;Langenmayr & Reiter, 2017 For each treated bank , we calculate the daily abnormal return , as the difference between the actual realized return , and the expected return , on trading day .…”
Section: Methodsmentioning
confidence: 99%